Huntington's Disease with Parkinson-Like Symptoms and Abnormal [123I] Ioflupane SPECT-CT (DaTs): A Case Report and Literature Review - Amro, Sarah; Punchihewa, Chamani; Bravo, Edina; Dizdarevic, Sabina (World Journal of Nuclear Medicine, 2025)
Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by an unstable expansion of CAG trinucleotide repeats that lead to progressive degeneration of postsynaptic striatal medium-spiny GABAergic neurons. We report a case of abnormal [123I] Ioflupane single-photon emission computed tomography/computed tomography (DaTSCAN) and a subsequent genetic test confirming HD. A 68-year-old man presented with progressive memory difficulties, auditory hallucinations, nightmares, suicidal thoughts, low mood, and involuntary limb movements. DaTSCAN showed borderline reduced putaminal binding ratios bilaterally, more prominent on the left side, and a low putamen-to-caudate ratio suggesting degenerative parkinsonism. Genetic testing revealed one pathogenic expansion (40/17 CAG repeats), confirming HD. Postsynaptic dopaminergic involvement has previously been documented in postmortem studies. However, an emerging in vivo research also suggests presynaptic dopaminergic involvement. While genetic testing remains the gold standard for diagnosis of HD, DaTSCAN may play a role in assessing dopamine transporter activity and tracking the progression of neurodegeneration in HD.
Keywords: Huntington's disease; DaTSCAN; dopamine transporter imaging; neurodegeneration; [123I] Ioflupane